Response Surface Methodology Optimization of Time-Resolved Fluorescence Immunoassay for Rapid Detection of AflatoxinB1 in Yellow Rice Wine - Mengjie Zhu; Dun Wang; Du Wang; Jing Dong; Xue Wang; Qi Zhang; Man Xiao (Toxins)
Yellow rice wine is susceptible to aflatoxinB1 (AFB1) contamination, yet existing detection technologies suffer from limitations such as high false-positive rates, cumbersome operational protocols, or elevated costs, rendering them inadequate for large-scale screening requirements. Consequently, the development of a highly sensitive and rapid detection method for AFB1 is urgently needed to provide technical support for quality supervision and risk assessment of yellow rice wine. In this study, AFB1 detection was performed using time-resolved fluorescence immunoassay technology, with quantitative analysis based on the ratio of the T signal value of the detection line to the C signal value of the quality control line and the natural logarithmic value of the standard solution concentration. Statistical experimental designs were used to optimize the process of this rapid detection of AFB1 in yellow rice wine. The most important factors influencing recovery rate (p < 0.05), as identified by a two-level Plackett-Burman design with 11 variables, were methanol-water volume fraction, sample to extraction solvent ratio, heating temperature, and heating time. The steepest ascent method was employed to identify the optimal regions for these four key factors. Central composite design (CCD) coupled with response surface methodology (RSM) was subsequently utilized to further explore the interactive effects among variables and determine their optimal values that maximize the recovery rate. The analysis results indicated that interactions between methanol-water volume fraction and other three factors–sample to extraction solvent ratio, heating temperature, heating time–affected the response variable (recovery rate) significantly. The predicted results showed that the maximum recovery rate of AFB1 (97.35%) could be obtained under the optimum conditions of a methanol-water volume fraction of 78%, a sample to extraction solvent ratio of 1:3.2, a heating temperature of 34 °C, and a heating time of 6.4 min. These predicted values were further verified by validation experiments. The excellent correlation between predicted and experimental values confirmed the validity and practicability of this statistical optimum strategy. Optimal conditions obtained in this experiment laid a good foundation for further use of time-resolved fluorescence immunoassay for rapid detection of AFB1 in yellow rice wine, demonstrating broad application prospects.